Front Cover: Carbon with Surface‐Enriched Nitrogen and Sulfur Supported Au Catalysts for Acetylene Hydrochlorination (ChemCatChem 3/2019). Issue 3 (7th February 2019) - Wang, Bolin; Zhao, Jia; Yue, Yuxue; Sheng, Gangfeng; Lai, Huixia; Rui, Jiayao; He, Haihua; Hu, Zhong‐ting; Feng, Feng; Zhang, Qunfeng; Guo, Lingling; Li, Xiaonian
Abstract : The Front Cover shows carbon with surface‐enriched nitrogen and sulfur supported Au catalysts for acetylene hydrochlorination. In their Full Paper, Bolin Wang et al. demonstrate that the sulfur species on the carbon surface was considered to be able to selective formation of pyrrolic nitrogen against pyridinic nitrogen, which significantly influence the catalytic performance of Au‐based catalysts. More information can be found in the Full Paper by Bolin Wang et al. on page 1001 in Issue 3, 2019 (DOI: 10.1002/cctc.201801555 ).